PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PT. POS INDONESIA (PERSERO) KABUPATEN BIREUEN - Yanto, Ferri; Yanti, Ira Dama; Akmal, Muhammad (Fakultas Ekonomi, 2024)
This study was conducted to analyze the effect of Work Environment and Compensation on Employee Performance, by taking the number of respondents as a research sample of 31 respondents who are employees who work at PT Pos Indonesia (Persero) Bireuen Regency to distribute questionnaires. The analysis method used in this research is multiple linear regression analysis where this analysis can be used to see the relationship and influence between variables. Based on the analysis and calculation of the research results, a strong and positive relationship was obtained between the Work Environment and Compensation on Employee Performance, with a correlation coefficient of 0.812 and a linear equation Y = 1.892 + 0.375 X1 + 0.439 X2. The results showed that there was a partial and simultaneous influence between the Work Environment and Compensation on Employee Performance. In this case 66% of the performance of employees of PT Pos Indonesia (Persero) Bireuen Regency can be explained by the variables of Work Environment and Compensation. The remaining 34% is influenced by other variables outside this study.Keywords: Work Environment, Compensation, Employee Performance